Fracture Analysis of a Cycloidal Gearbox as a Yaw Drive on a Wind Turbine - Martins, Jairo Aparecido; Romao, Estaner Claro (Engineering, Technology & Applied Science Research, 2024)
Fast growth of renewable energies has required addressing challenges such as generating the largest energy production possible throughout the equipment’s lifespan and between its preventive and corrective maintenance intervals. Actions such as preventive maintenance, and improvement of the main components, mainly when it comes to reliability and predictability are of extreme importance to reach maximum generation. Due to the importance of the yaw drives for wind turbines, this paper aims to evaluate a failure that occurred on a cycloidal gearbox used in a drive of this kind. For the evaluation of the yaw drive, all the components were analyzed to determine the incurred fracture mechanism. Such analysis was performed by mapping all components, conducting a hardness test to check the components’ mechanical properties, analysis of the fractured surfaces of the cycloidal disc, and numerical simulation (linear elastic) via the Finite Element Method (FEM) to check the stress distribution on the fractured part (cycloidal disc) under load, and theoretical calculation of the cycloidal disc lifespan. In addition, the stress distribution by FEM was compared with the broken regions of the physical part. To sum up, after all the evaluations, it is possible to claim the results demonstrate there was a premature fracture of the cycloidal disc that occurred due to the phenomenon of high cycle fatigue.